2014
DOI: 10.1371/journal.pone.0096837
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporally Restricted Expression of Cell Adhesion Molecules during Chicken Embryonic Development

Abstract: Differential cell adhesive properties are known to regulate important developmental events like cell sorting and cell migration. Cadherins and protocadherins are known to mediate these cellular properties. Though a large number of such molecules have been predicted, their characterization in terms of interactive properties and cellular roles is far from being comprehensive. To narrow down the tissue context and collect correlative evidence for tissue specific roles of these molecules, we have carried out whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…This is in contrast to mice which harbor a glutamic acid at position 16 of E-cadherin, preventing a successful interaction and hence invasion. A recent study could give a possible explanation of our results (Roy and Bandyopadhyay, 2014 ). In that work, the authors showed that the expression of the mRNA encoding E-cadherin was high early during the chicken development in all examined tissues, but diminished in chicken embryos older than 6 days.…”
Section: Discussionsupporting
confidence: 61%
“…This is in contrast to mice which harbor a glutamic acid at position 16 of E-cadherin, preventing a successful interaction and hence invasion. A recent study could give a possible explanation of our results (Roy and Bandyopadhyay, 2014 ). In that work, the authors showed that the expression of the mRNA encoding E-cadherin was high early during the chicken development in all examined tissues, but diminished in chicken embryos older than 6 days.…”
Section: Discussionsupporting
confidence: 61%
“…The remarkable cell patterns that arise in GCE through X-linked inheritance of inactive forms of the Pcdh19 gene leaves little doubt that it plays an important role in cell adhesion (Pederick et al, 2018). d-protocadherins also display expression patterns that differentially track tissue structures (Etzrodt et al, 2009;Redies et al, 2005), and for which changes in expression often precede the emergence of anatomical features in development Roy and Bandyopadhyay, 2014). Phenotypes potentially related to adhesion have been found for numerous other d-protocadherins, as well (Bononi et al, 2008;Cooper et al, 2015;Hayashi et al, 2014;Hayashi and Takeichi, 2015;Hoshina et al, 2013;Uemura et al, 2007;Zhu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A network of genes linked to IGF1, a positive regulator of cartilage ECM [49][50][51][52] , was identified within this network, including IGFBP3. Transcripts for the cell adhesion molecules CDH5,11 and 13, identified by STRING analysis, are also known to be expressed in the chick limb bud with CDH11 present from an early stage 53 . It is likely that the potassium voltage gated ion channels identified (KCNQ5, KCNA3, KCNE4, KCND3) may similarly be involved in ion balance and mechano-regulation.…”
Section: Protein-protein Interaction Analysis Of Ecm Organization Clumentioning
confidence: 99%